PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN PENDEKATAN KONTEKSTUAL PADA SISWA KELAS X MIA III SMA N 2 BANGKINANG KOTA - Hanardi Hanardi (Journal on Education, 2019)
Ability to write poem is included as one of the basic competence in Bahasa Indonesia of Grade X Senior High School. The students are expected to be able to write a poem based on the literature work components. On the contrary, the grade X MIA 3 SMA N 2 Bangkinang Kota commit difficulties in producing poem. It is as the consequence of the inappropriateness of learning approach. It is necessary to conduct a classroom action research (CAR) to solve the students’ problem. The subject of the research is grade X MIA 3. Writing poem test, observation sheet and interview guideline were employed as the instruments of the research. The findings showed that the students’ learning experience by using contextual approach in producing a peom is significantly improved.